GE_GERICHTE P/22571/2018 vom 18. August 2020 - GE Cour de justice (2020)
LÉSION CORPORELLE SIMPLE;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);VIOLATION DE DOMICILE | CP.123.al1.ch1; CP.123.al2.ch1; CP.144.al1; CP.186